2019
DOI: 10.1007/s42452-019-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesized amino-PEGylated silver decorated graphene nanoplatform as a tumor-targeted controlled drug delivery system

Abstract: In this study design, the PEGylated silver decorated graphene nanocomposites (NGO-AgNPs-PEG) were successfully prepared by eco-friendly non-toxic green synthesis following a novel syn-graphenization method using the aqueous leaf extract of Azadirachta indica (A. indica) (neem) as reducing agent. The prepared Smart pH stimuli responded nanoplatform was thoroughly characterized by various analytical techniques. Since a functional nanocarrier is very essential for cancer therapy, it could quickly guide the loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 74 publications
(118 reference statements)
1
15
0
Order By: Relevance
“…Motivated by the high plasmonic potential of Ag NPs, several strategies were suggested to preserve Ag nanostructure from the fast degradation [116]. These strategies mostly focus on surface modification of Ag NPs with an extra protecting layer of inorganic or organic coating, such as Si [117], graphene oxide (GO) [118], self-assembled monolayers of organic thiols [119], etc. Another approach to protect the unstable Ag NPs involves Au coating.…”
Section: Silver Npsmentioning
confidence: 99%
“…Motivated by the high plasmonic potential of Ag NPs, several strategies were suggested to preserve Ag nanostructure from the fast degradation [116]. These strategies mostly focus on surface modification of Ag NPs with an extra protecting layer of inorganic or organic coating, such as Si [117], graphene oxide (GO) [118], self-assembled monolayers of organic thiols [119], etc. Another approach to protect the unstable Ag NPs involves Au coating.…”
Section: Silver Npsmentioning
confidence: 99%
“…Recently, the biosynthesis of metal nanoparticles (MNPs) have been proposed as a cost-effective and eco-friendly substitute to chemical methods. Many studies have been demonstrated the biosynthesis of AgNPs mediated by the microorganism or by phytochemicals or enzymatic synthesis [11,18,19,[29][30][31][32][33]. Among the biological methods, photosynthesis which involves reduction by phytochemicals derived from plants seems to be the superior choice.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, they were also serving their purpose in food processing industry [55]. Recently there are research reports demonstrating the applications of AgNPs in the fields of targeted drug delivery [56], stem cell therapy [57], therapeutics [30] and cell imaging [55]. This is because of their cytotoxic [58], optical surface plasmon absorption and surface plasmon light scattering properties [38].…”
Section: Biomedicalmentioning
confidence: 99%